Development of an Integrated Dairy Supply Chain Model in Cooperative Systems: A Strategic Framework Positioning Cooperatives as the Hub of Efficiency, Value Creation, and Sustainability: Development of an Integrated Dairy Supply Chain Model in Cooperative Systems: A Strategic Framework Positioning Cooperatives as the Hub of Efficiency, Value Creation, and Sustainability - Pothawong, Naiyana (RATANABUTH JOURNAL, 2026)
This academic article aims to develop an Integrated Dairy Supply Chain Model for cooperative systems and to propose a strategic framework that positions cooperatives as the central hub for connecting stakeholders to enhance supply chain efficiency, value creation, and sustainability. The study employed a documentary research approach by analyzing and synthesizing knowledge derived from relevant concepts, theories, and literature, including Supply Chain Management (SCM), the Value Chain concept, Cooperative Theory, Institutional Economics, Transaction Cost Theory, Bargaining Power Theory, and Sustainable Supply Chain Management (SSCM). These theoretical foundations were integrated to explain the systemic relationships among key factors influencing the performance and development of dairy supply chains within cooperative systems. The synthesis revealed that dairy supply chains in cooperative systems continue to face several structural challenges, including information asymmetry, coordination failures, high transaction costs, governance gaps, and unequal bargaining power. These limitations undermine operational efficiency, equitable value distribution, and the competitiveness of smallholder dairy farmers. To address these challenges, the study proposes that cooperatives should function as a Strategic Hub, integrating material, information, and financial flows, while facilitating institutional coordination among all supply chain stakeholders. Through the integration of information, operational processes, and governance mechanisms, cooperatives can improve operational efficiency, reduce transaction costs, strengthen collaborative value creation, and promote long-term sustainability. The principal knowledge contribution of this article is the development of the Integrated Dairy Cooperative Supply Chain Model (IDCS Model). The model presents an integrated strategic framework comprising four interrelated dimensions: (1) Integration, (2) Efficiency, (3) Value Creation, and (4) Sustainability. It positions cooperatives as the strategic center for coordinating stakeholder collaboration and managing supply chain activities through a dynamic systems perspective. The proposed model provides a strategic framework that can be applied to other agricultural supply chains and serves as a valuable reference for policymakers and practitioners seeking to strengthen competitiveness, improve supply chain governance, and foster sustainable agricultural development.